Impact of Diversity in Training Resources on Self-Confidence in Diagnosing Skin Conditions Across a Range of Skin Tones: An International Survey - Buonsenso, Danilo; Liu, Jo-Fen; Shanmugavadivel, Dhurgshaarna; Davis, Tessa; Roland, Damian (Frontiers in Pediatrics, 2022)
Background Medical images are invaluable in facilitating recognition of clinical signs. Recent studies highlight a lack of diversity of skin tone images used within medical education. However, there is a paucity of data on the impact of this on patient care. Aims To investigate diversity in training resources used by users of an International online teaching platform and self-confidence in diagnosing skin conditions in all skin tones. Methods Users of an online teaching platform (www.dftbskindeep.com) were invited to participate in a survey evaluating key points including geographical location, ethnicity, profession, specialty, years of experience, training resources and confidence in diagnosing skin conditions. Data analyses were performed using SPSS. Categorical variables were presented as proportions. Chi-squared or Fisher's exact tests were used to compare the distribution between groups as appropriate. Results Of 600 participants, 74% reported training resources featuring predominantly white skin. Participants were “generally uncertain” in 43% cases, “sometimes uncertain but clinically safe” (52%), and “confident across a range of skin tones” in a minority (5%). Self-confidence was associated with location [higher in Africa (29%) and Latin America (11%), (p < 0.001)]; diversity of training resources [higher with a mix (10%) or darker tones (20%) (p < 0.001)]; clinical experience [6–10 (5%) or >10 years of practice (11%) (p < 0.001)] and specialty [highest in dermatologists (53%, p < 0.001)]. Self-confidence was lowest among pediatricians, emergency medicine and pediatric emergency medicine specialists (<5%). Conclusions These data provide preliminary evidence that training resources used by healthcare professionals on a global scale may lack enough diversity on representation of skin images, and a lack of self-confidence in diagnosing pediatric skin conditions. Further work is needed to understand the impact on knowledge and patient care to ensure equitable healthcare for all.